Demand side factors affecting financial inclusion in Vietnam - Thu, Huong Tran Thi (Edelweiss Applied Science and Technology, 2025)
This study aims to identify the determinants influencing financial inclusion in Vietnam and to propose relevant policy recommendations aligned with Vietnam’s National Financial Strategy on financial inclusion. Using quantitative analysis methods, the study employs data from the 2022 Vietnam Household Living Standards Survey (VHLSS), conducted by Vietnam’s General Statistics Office (GSO). The results of the model of factors affecting financial inclusion in Vietnam indicate that gender has a negative impact on account ownership, access to savings services, use of ATM cards, use of credit cards, and access to investment and insurance services. The variables Age and Age² exhibit positive and negative correlations, respectively, confirming a non-linear relationship between age and financial inclusion measures. Additionally, marital status, education, income, and internet access show positive and statistically significant impacts. These findings highlight the necessity of targeted financial literacy programs, gender-sensitive policy interventions, and enhanced digital infrastructure. Practically, these implications assist policymakers in designing effective strategies to foster comprehensive financial inclusion, thereby contributing to Vietnam’s sustainable economic growth and financial stability.